Gas Nozzle Effect on the Deposition of Polysilicon by Monosilane Siemens Reactor - Seung Oh Kang; Uk June Lee; Seung Hyun Kim; Ho Jung You; Kun Park; Sung Eun Park; Jong Hoon Park (International Journal of Photoenergy)
Deposition of polysilicon (poly-Si) was tried to increase productivity of poly-Si by using two different types of gas nozzle in a monosilane Bell-jar Siemens (MS-Siemens) reactor. In a mass production of poly-Si, deposition rate and energy consumption are very important factors because they are main performance indicators of Siemens reactor and they are directly related with the production cost of poly-Si. Type A and B nozzles were used for investigating gas nozzle effect on the deposition of poly-Si in a MS-Siemens reactor. Nozzle design was analyzed by computation cluid dynamics (CFD). Deposition rate and energy consumption of poly-Si were increased when the type B nozzle was used. The highest deposition rate was 1 mm/h, and the lowest energy consumption was 72 kWh⋅kg-1 in this study.